A Framework for Teaching Business Ethics - Oddo, Alfonso R. (Journal of business ethics, 1997)
What ethical framework should be used as a basis for teaching business ethics? Should business ethics be taught by ethicists in a separate course, by business faculty in business courses, or perhaps by both? These are some of the issues this paper will address. The paper begins with a review of the literature concerning approaches to teaching business ethics. Next, some ethical frameworks for teaching business ethics are considered. Finally, the paper proposes that students should apply their own personal values to business ethical issues in the classroom, thus providing future business leaders with a process for resolving ethical dilemmas.